2013
DOI: 10.3389/fendo.2013.00049
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Melanin-Concentrating Hormone and Its Receptors in Energy Homeostasis

Abstract: Extensive studies in rodents with melanin-concentrating hormone (MCH) have demonstrated that the neuropeptide hormone is a potent orexigen. Acutely, MCH causes an increase in food intake, while chronically it leads to increased weight gain, primarily as an increase in fat mass. Multiple knockout mice models have confirmed the importance of MCH in modulating energy homeostasis. Animals lacking MCH, MCH-containing neurons, or the MCH receptor all are resistant to diet-induced obesity. These genetic and pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 134 publications
(231 reference statements)
0
60
0
Order By: Relevance
“…Similarly, in the hypothalami of Bbs2 − / − and Bbs4 − / − mice, ACIII + cilia appear normal in number and length; however, neither SSTR3 nor MCHR1 is recruited to neuronal cilia . Several studies have shown a role for MCH, MCH + neurons, and MCHR1 in energy homeostasis . On the other hand, loss of function renders the mice resistant to diet‐induced obesity (DIO) and does not result in hyperphagia or increased fat mass.…”
Section: Primary Ciliary Function and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in the hypothalami of Bbs2 − / − and Bbs4 − / − mice, ACIII + cilia appear normal in number and length; however, neither SSTR3 nor MCHR1 is recruited to neuronal cilia . Several studies have shown a role for MCH, MCH + neurons, and MCHR1 in energy homeostasis . On the other hand, loss of function renders the mice resistant to diet‐induced obesity (DIO) and does not result in hyperphagia or increased fat mass.…”
Section: Primary Ciliary Function and Obesitymentioning
confidence: 99%
“…43 Several studies have shown a role for MCH, MCH + neurons, and MCHR1 in energy homeostasis. 44 On the other hand, loss of function renders the mice resistant to diet-induced obesity (DIO) and does not result in hyperphagia or increased fat mass. Consequently, it is not clear how a lack of ciliary MCHR1 would contribute to obesity, assuming that ciliary localization is necessary for proper MCHR1 function.…”
Section: Primary Ciliary Function and Obesitymentioning
confidence: 99%
“…To better understand the role of MCH-MCHR1 system in energy homeostasis, several structurally distinct small molecule antagonists for the MCHR1 have been synthesized and tested in cell-based assays for their selectivity and for in vivo potency in the rodent. Comprehensive review of desired selectivity and efficacy of MCHR1 antagonist in vivo should consult some recent reviews (38, 39). The majority of studies indicated that the MCHR1 antagonists are effective in different models of obesity in a variety of different rodent strains, due to inhibition of food intake and/or energy expenditure (40, 41).…”
Section: Mch Acts Through Gpcrsmentioning
confidence: 99%
“…Melanin-concentrating hormone (MCH) is a cyclic neuropeptide that consists of 19 amino acids, derived from a 165-amino acid preprohormone encoded by the Pmch gene. MCH exerts its effects through MCHR1 and MCHR2 receptors, which are also G protein-coupled receptors [1112]. MCH neurons are distributed adjacent to orexin neurons in the lateral hypothalamus, and MCH neurons also project throughout the brain [1314].…”
Section: Introductionmentioning
confidence: 99%